2004
DOI: 10.1021/cm049517q
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Electronic Junctions

Abstract: A review with 228 references on experimental investigation of conductor/molecule/metal molecular electronic junctions is presented. Devices based on covalent and LangmuirBlodgett bonding of single molecules or molecular monolayers to conducting substrates are reviewed, as characterized by scanning probe microscopy and microelectronic techniques. Phenomena observed to date include molecular rectification, conductance switching, and nonlinear current/voltage behavior. Prospects and problems for the application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
533
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 523 publications
(556 citation statements)
references
References 225 publications
(602 reference statements)
20
533
1
2
Order By: Relevance
“…sensors and biochips, 2,3 photovoltaics, 4,5 fuel cell, 6 biomaterials, 7 and molecular electronics, 4,8,9 as well as to provide fundamental understanding of electron transfer, 10 controlling reactions at surfaces, 11 and tailoring surface properties. 12 Among the many exciting developments, a number of rather sophisticated molecular assemblies have been developed that not only involve organic and organometallic molecules, but also nanomaterials and/or biomolecules.…”
Section: Simone Ciampimentioning
confidence: 99%
“…sensors and biochips, 2,3 photovoltaics, 4,5 fuel cell, 6 biomaterials, 7 and molecular electronics, 4,8,9 as well as to provide fundamental understanding of electron transfer, 10 controlling reactions at surfaces, 11 and tailoring surface properties. 12 Among the many exciting developments, a number of rather sophisticated molecular assemblies have been developed that not only involve organic and organometallic molecules, but also nanomaterials and/or biomolecules.…”
Section: Simone Ciampimentioning
confidence: 99%
“…30 Frisbie et al 37 showed that the mechanism of charge transport in junctions with conjugated molecular wires changes from tunneling to hopping as the molecular length increases. Used a conducting tip of an atomic force microscope as the top contact, they measured the conductivities of a series of oligophenyleneimines (OPI), with lengths ranging from 1.5 to 7.3 nm, immobilized on gold bottom-electrodes.…”
Section: Mechanisms Of Charge Transport Across Sams Three Different mentioning
confidence: 99%
“…i) At high voltages across the SAM (V > ~ 2.0 V) the SAM-based junctions have a mechanism of charge transport (field emission) that is different from the mechanism at low voltages (hopping and tunneling). 30 The half-wave rectifier ( Figure 1D) incorporating these molecular diodes rectifies at input voltages less than 2.4 V, but does not rectify at high input voltages in the range of 2.4 -10 V (these voltages are specific to the circuit and depend on the choice of resistor). ii) In operation, these molecular diodes have large internal resistances (~10 6 Ω), suffer limited lifetimes (here 30-40 min in operation at 50 Hz), and break down outside of a relatively small window of applied bias (-5.0 to 2.2 V).…”
Section: Introductionmentioning
confidence: 99%
“…(10,11) The mechanisms (e.g., tunneling, inelastic hopping, or other processes) of CT through peptides are still incompletely defined, and have been variously suggested to depend on the length of the peptide, the presence of secondary structure, and the presence of specific side chains. (1,12,13) Rates of charge tunneling across SAMs composed of n-alkanethiolates have been studied extensively (14)(15)(16)(17)(18), and most commonly characterized using the parameters of the simplified Simmons equation (eq. 1).…”
mentioning
confidence: 99%